Scent and scent-orship in the nursery: why does it matter?. Issue 3 (3rd July 2021) - Albon, Deborah
ABSTRACT: Scent matters in the lives of humans (and other living creatures). However, thus far, it is largely unexplored in ethnographic work in education. Drawing on and adding to the literature on 'smellscapes' as a way of conceptualising space, this paper adds new insights into early childhood education and care (ECEC) by reporting on the differentials in scent between the staffroom and the baby room in a nursery in Central London. In so doing, the distinctive aromas of disinfectant and spices, which characterised these two spaces, are interrogated in order to consider children and educators' embodied experiences of scent as well as well as to evidence examples of generational and racial inequities.